Antigenic Analysis of Outer Membrane Proteins of Biofilm and Free Cells of Pasteurella multocida A:1 in Comparison with Local Isolate - Arun, S.J.; Krishnappa, G. (International Journal of Poultry Science, 2004)
Outer Membrane Protein (OMP) - enriched extracts of Pasteurella multocida A:1 (`A`) and local isolate (`L`) obtained from Nutrient rich free cell (FC), Nutrient deficient free cell (DC) and Biofilm cell (BC) growth were analyzed by SDS-PAGE. In general, the OMP profile in all the three growth conditions of `A` was different from that of `L` suggesting that both could be of different serotype. The FC, DC and BC derived OMPs of both `A` and `L` showed a significant variation suggesting that BC are demonstrably and profoundly different from their free cell counterparts (FC and DC). More than four unique proteins were observed in the OMPs of BC when compared to FC and DC. The western blot using Anti-BC hyperimmune serum, elicited maximum number of immunogens that were common to both `A` and `L`, including immunogens that were detected by Anti-DC and Anti-FC. Some unique proteins of biofilm cells were also found to be highly immunogenic. Since, fowl cholera is a biofilm associated disease the use of biofilm form of pathogen could be an alternative strategy for evolving effective immunoprophylaxis against fowl cholera.